1980
DOI: 10.1111/j.1365-2125.1980.tb01815.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic toxicity of pyrazolones: the problem of nitrosation.

Abstract: 1 During 6-month oral toxicity studies of dipyrone in rats and dogs, there was an increase in the number of reticulocytes and Heinz bodies at the highest dose, and a slight haemosiderosis was induced.2 Similar results were obtained after parenteral administration (intravenously and subcutaneously).3 These studies fail to contribute to the knowledge of the mechanism of allergic reactions in man.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
3

Year Published

1984
1984
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 2 publications
0
12
0
3
Order By: Relevance
“…Salivation, a possible indicator for nausea, and the most common side effect observed in this study, occurred in both groups. Salivation has been reported with metamizole (Kramer, 1980) but not with carprofen, so this may also be related to inhalational anaesthesia.…”
Section: Discussionmentioning
confidence: 88%
“…Salivation, a possible indicator for nausea, and the most common side effect observed in this study, occurred in both groups. Salivation has been reported with metamizole (Kramer, 1980) but not with carprofen, so this may also be related to inhalational anaesthesia.…”
Section: Discussionmentioning
confidence: 88%
“…Because previous treatment with dipyrone (also called metamizole) appeared frequently in our patients, it might be a possible contributing factor to the development of RWA. Studies on subacute and chronic toxicity of dipyrone in rats and dogs revealed increasing numbers of Heinz bodies and reticulocytes following administration (Kramer ).…”
Section: Discussionmentioning
confidence: 99%
“…A second in vivo micronucleus test was reported in the literature but gave no details beyond a statement that metamizole was positive. Published studies were also reported on the mutagenic potential of nitrosation products of metamizole in the in vitro assay for gene mutation in bacteria (Ames test); two studies claimed positive results, but the third, which was the most adequately reported, claimed negative results (16,40,55). in well-conducted mutagenicity assays (in vitro gene mutations and in vivo micronucleus test), which were carried out in compliance with the Good laboratory Practice and relevant oecD guidelines, it was concluded that metamizole was not genotoxic (30).…”
Section: Genotoxicitymentioning
confidence: 99%